2018
DOI: 10.4314/jfas.v9i6s.80
|View full text |Cite
|
Sign up to set email alerts
|

Fascicle behaviour analysis during forward lunge exercise: the comparisons between training loads

Abstract: This study was conducted to determine and compare the fascicle behaviour during forward lunge exercise with different loadings lifted. Thirty recreationally active, untrained men (mean age = 21 ± 0.83 years old) were recruited and were assigned to perform forward lunge with 30% 1RM (30FL) and 70% 1RM (70FL) with both their dominant and non-dominant leg. For both dominant and non-dominant leg, results showed that FLmax, FLmin, PAmax and PAmin were all greater during 70FL compared to 30FL, p < 0.001. However, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recent studies conducted by Nadzalan et al [5,6,[19][20][21]39] found that biomechanical responses were difference across variations of lunge protocols. The greater loads were found to cause more effects on the forces production when compared to the speed of movement.…”
Section: Biomechanical Analysis Of Lungementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted by Nadzalan et al [5,6,[19][20][21]39] found that biomechanical responses were difference across variations of lunge protocols. The greater loads were found to cause more effects on the forces production when compared to the speed of movement.…”
Section: Biomechanical Analysis Of Lungementioning
confidence: 99%
“…The inclusion of lunge as training exercises should be beneficial as it will allow athletes or individuals to train and improve their ability for the movement and as a way to overload the athletes or individuals, various methods of lunge could be implemented during training sessions [18]. This includes putting some weights and includes ballistic movement during the exercise [15,[19][20][21].…”
mentioning
confidence: 99%
“…Despite of its popularity, lack of research had been conducted on comparing the effects of performing different kinds of push up methods on muscle strength adaptations. As different techniques of performing exercises were shown to causes different acute responses (Cogley, Archambault, Fibeger, & Koverman, 2005;Kim, Yang, & Lee, 2018;Nadzalan, Azmi, et al, 2018;Nadzalan, Mohamad, Lee, Tan, et al, 2017;Nadzalan, Mohamad, Ahmad, & Waqqash, 2017;Nadzalan, Mohamad, Low, Tan, et al, 2017;Vila-Chã et al, 2017), it is believed that altering the movement techniques will cause different adaptations. Thus, the purpose of this study is to determine and compare the effects of two main kinds of push up training; namely i) traditional push up and ii) plyometric push up on muscular strength and muscular endurance performance.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle architectures have been found to be correlated with sport/exercise performance Earp et al, 2011;Earp et al, 2010;Kumagai et al, 2000;Nadzalan, Mohamad, Lee, & Chinnasee, 2016). Despite has been studied in other types of movements, to the authors' knowledge, the study of fascicle behaviour during lunge movement was scarce (Nadzalan, Mohamad, Low, Ahmad, & Waqqash, 2017). It is important to get to know the stimuli presented during the different methods of movement as it can affect the structural adaptations (Nadzalan, Mohamad, Lee, & Chinnasee, 2017).…”
Section: Introductionmentioning
confidence: 99%